Case report: Genotype and phenotype of DYNC1H1-related malformations of cortical development: a case report and literature review - Wen-Rong Ge; Pei-Pei Fu; Wei-Na Zhang; Bo Zhang; Ying-Xue Ding; Guang Yang; Guang Yang; Guang Yang (Frontiers in Neurology, 2023)
BackgroundMutations in the dynein cytoplasmic 1 heavy chain 1 (DYNC1H1) gene are linked to malformations of cortical development (MCD), which may be accompanied by central nervous system (CNS) manifestations. Here, we present the case of a patient with MCD harboring a variant of DYNC1H1 and review the relevant literature to explore genotype-phenotype relationships.Case presentationA girl having infantile spasms, was unsuccessfully administered multiple antiseizure medications and developed drug-resistant epilepsy. Brain magnetic resonance imaging (MRI) at 14 months-of-age revealed pachygyria. At 4 years-of-age, the patient exhibited severe developmental delay and mental retardation. A de novo heterozygous mutation (p.Arg292Trp) in the DYNC1H1 gene was identified. A search of multiple databases, including PubMed and Embase, using the search strategy DYNC1H1 AND [malformations of cortical development OR seizure OR intellectual OR clinical symptoms] up to June 2022, identified 129 patients from 43 studies (including the case presented herein). A review of these cases showed that patients with DYNC1H1-related MCD had higher risks of epilepsy (odds ratio [OR] = 33.67, 95% confidence interval [CI] = 11.59, 97.84) and intellectual disability/developmental delay (OR = 52.64, 95% CI = 16.27, 170.38). Patients with the variants in the regions encoding the protein stalk or microtubule-binding domain had the most prevalence of MCD (95%).ConclusionMCD, particularly pachygyria, is a common neurodevelopmental disorder in patients with DYNC1H1 mutations. Literature searches reveales that most (95%) patients who carried mutations in the protein stalk or microtubule binding domains exhibited DYNC1H1-related MCD, whereas almost two-thirds of patients (63%) who carried mutations in the tail domain did not display MCD. Patients with DYNC1H1 mutations may experience central nervous system (CNS) manifestations due to MCD.